Controlling w połączonych spółkach dystrybucyjnych - Kes, Zdzisław; Kubalańca, Leokadia (The Controlling at Joint Distributional Companies, 2005)
In the article were introduced questions relating to kelter of controlling. The sector of distribution of electrical energy begin the process of joining of companies, which extorts the change in controlling's working in these companies. These changes have to influence tasks and organization of controlling in a consolidated company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 327-334